Sexual and injection-related risks in Puerto Rican-born injection drug users living in New York City: A mixed-methods analysis - Gelpí-Acosta Camila; Hagan Holly; Jenness Samuel M; Wendel Travis; Neaigus Alan (BMC, 2011)
Abstract Background These data were collected as part of the National HIV Behavioral Surveillance (NHBS) study. NHBS is a cross-sectional study to investigate HIV behavioral risks among core risk groups in 21 U.S. cities with the highest HIV/AIDS prevalence. This analysis examines data from the NHBS data collection cycle with IDU conducted in New York City in 2009. We explored how the recency of migration from Puerto Rico (PR) to New York City (NYC) impacts both syringe sharing and unprotected sex among injection drug users (IDU) currently living in NYC. Methods We used a mixed-methods approach to examine differences in risk between US-born IDU, PR IDU who migrated to NYC more than three years ago (non-recent migrants), and PR IDU who migrated in the last three years (recent migrants). Respondent-driven sampling (RDS) was used to recruit the sample (n = 514). In addition, qualitative individual and group interviews with recent PR migrants (n = 12) and community experts (n = 2) allowed for an in-depth exploration of the IDU migration process and the material and cultural factors behind continued risk behaviors in NYC. Results In multiple logistic regression controlling for confounding factors, recent migrants were significantly more likely to report unprotected sexual intercourse with casual or exchange partners (adjusted odds ratio [AOR]: 2.81; 95% confidence intervals [CI]: 1.37-5.76) and receptive syringe sharing (AOR = 2.44; 95% CI: 1.20-4.97) in the past year, compared to US-born IDU. HIV and HCV seroprevalence were highest among non-recent migrants. Qualitative results showed that risky injection practices are partly based on cultural norms acquired while injecting drugs in Puerto Rico. These same results also illustrate how homelessness influences risky sexual practices. Conclusions Poor material conditions (especially homelessness) may be key in triggering risky sexual practices. Cultural norms (ingrained while using drugs in PR) around injection drug use are perpetuated in their new setting following an almost natural flow. These norms may have a particular stronghold over risky drug injection practices. These results indicate that culturally appropriate HIV and HCV prevention and education services are needed. In addition, homelessness should be addressed to reduce risky sexual practices.